Analisis Strategi BMT El-Itqan Lubuk Malako dalam Menjembatani Akses Pembiayaan UMKM untuk Menghindari Ketergantungan pada Rentenir - Melifidia Sofyan; Yefri Joni (Lembaga Yasin AlSys, 2026)
The dependence of micro, small, and medium enterprise (MSME) actors on moneylenders remains an important issue in strengthening the community economy, while studies that specifically discuss the strategies of Islamic microfinance institutions in bridging financing needs at the local level remain limited. This study aimed to analyze the factors that lead MSME actors to prefer moneylenders and to evaluate the strategies of KSPPS BMT El-Itqan Lubuk Malako in providing alternative financing that meets community needs. This study used a qualitative approach with a case study design, involving a number of informants consisting of MSME actors and BMT managers selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using inductive thematic analysis techniques. The results showed that ease of access, speed of fund disbursement, and minimal administrative requirements were the main reasons MSME actors chose moneylenders, although the interest charged was relatively high and had a negative impact on business sustainability. On the other hand, BMT El-Itqan has played a role as a Sharia-based financing alternative, but still faces limitations in service speed and financing flexibility. These findings contribute to the development of consumer behavior theory and the Theory of Planned Behavior in the context of Islamic microfinance, while also broadening understanding of financing behavior among rural communities. The conclusion of this study confirms the importance of improving accessibility, service speed, and financial literacy to strengthen the role of BMT as a more adaptive financing alternative for MSME actors.